PENDEKATAN CONTENT AND LANGUAGE INTEGRATED LEARNING DALAM PEMBELAJARAN TEKS PROSEDUR BAHASA INDONESIA - Safitri, Nur Anita Syamsi; Asdah, Atikah Nurul; Rasdin, Rafika (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2024)
The Content and Language Integrated (CLIL) approach promotes teaching and learning that combines content and language. To be able to integrate the two well, a strong foundation is needed. This research aims to describe the basic concepts of the CLIL approach as an educational approach that has a dual focus and examples of its application in Indonesian language learning, especially procedural texts. Literature study is used as a research method. Data collected to answer questions and achieve research objectives comes from printed books, electronic books, journals, scientific articles, and educational curriculum syllabi that apply in Indonesia. The research results show that the CLIL approach is famous for the 4C concept (Cognitive, Content, Culture, Communication). When applied in learning Indonesian procedural texts, there are similarities and differences between knowledge and skills competencies. The difference lies in the cognitive and communication concepts, while the similarities lie in the concepts of content and culture.